Exploration ethnomathematics in the SAS program (Arek Suroboyo School) math game at SMP Negeri 13 Surabaya - Yunitasari, Luthfia; Kirana, Nabilla Sasi; Febrina, Aulia Eka; Sadieda, Lisanul Uswah; Suprijatno, Suprijatno (Institute of Computer Science (IOCS), 2025)
This study aims to describe the mathematical concepts contained in the PENGMATIKA game at SMP Negeri 13 Surabaya as well as students' responses after participating in the game. This research uses a qualitative approach with an ethnographic method, employing data collection techniques such as in-depth interviews, documentation, and observations involving teachers and students. The results show that the PENGMATIKA game contains mathematical concepts such as flat shapes including squares, rectangles, rhombuses, as well as circle nets. Students stated that learning through PENGMATIKA made it easier to understand flat shapes, solid shapes, and nets. This study contributes to the development of mathematics learning by demonstrating that traditional games can be used as an engaging and effective educational medium in schools.